The "Optimum Tariff" and the Cost of Exports - Polak, J. J. (Review of Economic Studies, 1951)
Journal Article The “Optimum Tariff” and the Cost of Exports Get access J. J. Polak J. J. Polak Washington, D.C. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 19, Issue 1, 1950, Pages 36–41, https://doi.org/10.2307/2296269 Published: 01 December 1950